Addiction Frameworks and Support for Expanding Treatment for Drug Offenders. (September 2017) - Murphy, Jennifer
This study examined how a respondent's addiction framework (i.e., whether they conceptualized addiction as a medical–social or a moral problem) was associated with their attitudes toward expanding treatment for drug offenders via funding for California's Proposition 36. Using a 2012 California Field Poll, the author created scales to assess an individual's addiction framework. Logistic regression was used to assess how well the addiction frameworks correlated with support for expanding Proposition 36. Results showed that those who held a stronger medical–social framework for conceptualizing addiction were more likely to support the expansion of Proposition 36, while those who perceived addiction as a moral problem were less likely to support the expansion of Proposition 36. Addiction frameworks were strongly related to policy attitudes even after controlling for many other factors, including race and political ideology. How one conceptualizes addiction is a key factor for understanding their views on drug policy.